Social Media Effects on E-Commerce Activities: The Case of Kuwait during and following the COVID-19 Pandemic - Hamad AlWazzan (Proceedings, 2023)
This paper discusses the impact of social media on the e-commerce industry in Kuwait. The paper highlights the slow growth of e-commerce in the region due to traditional shopping practices and lack of knowledge about e-commerce instruments. The paper explores the potential of e-commerce in Kuwait and how social media platforms like Facebook and Instagram are contributing to its growth. The paper also highlights the efforts of the Kuwaiti government in enhancing its e-Government potential and adopting laws in line with international regulations to make e-commerce more efficient and secure. Finally, the paper discusses the growth of regional-wide platforms in Kuwait and the shift towards the integration of digital technologies into the national economy.